Tren Akun Instagram Lambe Turah sebagai Pemicu Kontroversi Ditinjau dari Perspektif Hadis - Nadhiran, Hedhri; Riswana, Amanda Tria (Jurnal Riset Agama, 2022)
The latest news is not only obtained from television shows, but also through gossip accounts on social media. One of them is an account called @lambeturah. The purpose of this study is to discuss the Lambe Turah Instagram account as a trigger for controversy from the perspective of the hadith of the Prophet Saw. About liars who convey information that is not necessarily true and exaggerate the information. This type of research uses qualitative methods, namely the method of analyzing data not in the form of numbers using a library research approach. This study concludes that in this Instagram account tren there is an element of lies, this can be seen from the delivery of news which is only based on assumptions. It can also be seen from the description of the hadith about the delivery of authentic quality news that the Prophet Saw. taught us to say good things and be silent. This study recommends to the public as a guide before receiving news, to be more careful in using social media.